المسائل الفقهية المبنية على الترجيح بمقصد الوسيطة عند الشيخ ابن عثيمين في كتابه: الشرح الممتع على زاد المستقنع - السويداء، مها بنت سالم بن إبراهيم (جامعة أم القرى, 2023)
يهدف البحث إلى تسليط الضوء على المسائل الفقهية المبنية على الترجيح بمقصد الوسطية عند الشيخ ابن عثيمين في كتابه (الشرح الممتع على زاد المستنقع)، وهذا البحث عبارة عن دراسة فقهية مقاصدية يتجلى فيها الاهتمام بالفقه المقاصدي من خلال ربط المسائل الفقهية بمقاصد الشريعة ومقصد الوسطية خاصة في الأبواب الفقهية وإبراز دور الشيخ ابن عثيمين في الاهتمام بالمقاصد الشرعية باعتماده على مقصد الوسطية والاعتدال في الترجيح واعتبار مقصد الوسطية مرجحا شرعيا في المسائل الخلافية والاجتهادية، وقد تضمن البحث مقدمة وتشمل على مدخل تعريفي بالموضوع وأهميته ومنهجه وخطته، وثلاثة مباحث وخاتمة، وفقا لما يلي: المبحث الأول: ويتضمن نبذة مختصرة عن الشيخ محمد بن صالح العثيمين رحمه الله. والمبحث الثاني: في مفهوم مقصد الوسطية متضمنا تعريف كل من المقاصد الشرعية، ومقصد الوسطية، موضحا التأصيل الشرعي لمقصد الوسطية ومفهوم الترجيح بمقصد الوسطية في المسائل الاجتهادية. ثم كان المبحث الثالث: في المسائل الفقهية المبنية على الترجيح بمقصد الوسطية عند الشيخ ابن عثيمين رحمه الله في كتابه (الشرح الممتع على زاد المستقنع) تعرضت فيه بالجمع والدراسة الفقهية للمسائل المندرجة في أبواب الفقه المختلفة مبينة من خلال الدراسة نص الترجيح بمقصد الوسطية وأقوال الفقهاء ووجه الوسطية في الترجيح، ثم ذيل البحث بخاتمة أجمل فيها أهم النتائج والتوصيات. The research aims to shed light on Fiqh (jurisprudential) issues based on the most preponderant opinion with the inten-tion of moderation, according to Sheikh Ibn Uthaymeen in his book "al-Sharh al-Mumti’ ala Zad al-Mustaqnie". This research a purposeful jurisprudential study in which interest in purposeful jurisprudence is shown through the link be-tween jurisprudence issues and the purposes of Sharia and the purpose of moderation, especially in jurisprudential mat-ters, and highlighting the role of Sheikh Ibn Uthaymeen in paying attention to the legitimate purposes by relying on the purpose of moderation in preference and considering the purpose of moderation as a legitimate weight in the controver-sial and discretionary issues. The research included an introduction that includes an introduction to the subject, its im-portance, methodology and plan, three sections and a conclusion, as follows: The first section consists of a brief de-scription of Sheikh Muhammad bin Saleh Al-Uthaymeen, may God have mercy on him. The second section dealt with the concept of the purpose of moderation, including the definition of both the legitimate purposes and the purpose of moderation, explaining the legal rooting of the purpose of moderation and the concept of preference with the intent of moderation in discretionary issues. The third topic addressed the preference-based jurisprudential problems with the intention of moderation that Sheikh Ibn Uthaymeen, may God have mercy on him, dealt with in his book "al-Sharh al-Mumti’ ala Zad al-Mustaqnie". Also, in this topic, the researcher dealt with issues from the various jurisprudence chap-ters by collection and jurisprudential study and showed through the study the text of preference with the purpose of moderation, the sayings of the jurists and the face of moderation for preference, and the research concluded with a con-clusion in which the most important results and recommendations were summarized.
Keywords: الشريعة الإسلامية -- الأحكام الفقيه -- ابن العثيمين، محمد بن صالح، ت. 2001 م. -- أصول الفقه